Bacia do Parnaíba: aspectos morfológicos - Andrade, Gilberto Osório de; Lins, Rachel Caldas (Ciência & Trópico, 2011)
RESUMOCom as peculiaridades geomorfológicas decorrentes do fato de se achar totalmente numa bacia sedimentar, a bacia hidrográfica do Parnaíba tem sua topografia descrita e explicada geneticamente. Identificam-se os aplanamentos cenozóicos, experimenta-se um inventário dos interflúvios alto, médio e baixos – estes últimos representados por níveis de erosão quaternários – e fazem-se indicações, também, de interesse turístico bem como de diferentes sítios urbanos. O fácil traçado das rodovias se deve às particularidades topográficas.ABSTRACTMorphologic aspects of the Parnaíba basin. v. 5, n. 1, p. 49-63, jan./jun. 1977.With the geomorphologic particularities originated from the fact of being almost totally located, the hydrographical basin of Parnaíba in a sedimentary basin, it has its topography genetically described and explained. The cenozoic levellings are identified, an inventory of the high, medium and low dividing area amongst the basins, is experimented – these latter represented by quaternary levels of erosion – and are also made indications of touristic interest as well as of different urban places. The easy out line of the roads is due to the topographical particularities.RESUMÉAspects morphologiques du basin du Parnaíba. v. 5, n. 1, p. 49-63, jan./jun. 1977.Avec les particularités géomorphologiques découlant du fait qu’il se trouve presque entièrement dans un basin sédimentaire, le basin hydrographique du Parnaíba a sa topographie décrite et expliquée génétiquement. On y identifie les aplanissements cénozoiques, on y esquisse un inventaire des interfluves haut, moyen et bas – ces derniers représentés par des niveux d’érosion quaternaires – et on y fait aussi des indications d’intérêt touristique, ainsi que de différents sites urbains. La trace facile des routes se doit également aux particularités topographiques.